2010
DOI: 10.1073/pnas.0914428107
|View full text |Cite
|
Sign up to set email alerts
|

Direct regulation of phytoene synthase gene expression and carotenoid biosynthesis by phytochrome-interacting factors

Abstract: Carotenoids are key for plants to optimize carbon fixing using the energy of sunlight. They contribute to light harvesting but also channel energy away from chlorophylls to protect the photosynthetic apparatus from excess light. Phytochrome-mediated light signals are major cues regulating carotenoid biosynthesis in plants, but we still lack fundamental knowledge on the components of this signaling pathway. Here we show that phytochrome-interacting factor 1 (PIF1) and other transcription factors of the phytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
340
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(362 citation statements)
references
References 42 publications
(83 reference statements)
19
340
3
Order By: Relevance
“…The fact that GNC and GNL transcript levels are increased in pif mutant backgrounds suggests that GNC and GNL may be direct transcriptional repression targets of PIFs. This model is also supported by a recent gene expression study in which GNC and GNL were found to be repressed following PIF1 overexpression (Oh et al 2009), and another study that reveals that PIFs can act as transcriptional repressors as well as transcriptional activators (Toledo-Ortiz et al 2010). Since gnc and gnl mutants have a germination defect, and since PIF1 is the major PIF factor controlling germination, it may be that PIF1 controls germination by regulating GNC and GNL expression.…”
Section: Discussionsupporting
confidence: 61%
“…The fact that GNC and GNL transcript levels are increased in pif mutant backgrounds suggests that GNC and GNL may be direct transcriptional repression targets of PIFs. This model is also supported by a recent gene expression study in which GNC and GNL were found to be repressed following PIF1 overexpression (Oh et al 2009), and another study that reveals that PIFs can act as transcriptional repressors as well as transcriptional activators (Toledo-Ortiz et al 2010). Since gnc and gnl mutants have a germination defect, and since PIF1 is the major PIF factor controlling germination, it may be that PIF1 controls germination by regulating GNC and GNL expression.…”
Section: Discussionsupporting
confidence: 61%
“…The organic bottom phase was collected and dried in a SpeedVac at room temperature. The samples were resuspended in 50 to 150 mL of ethyl acetate, and then 750 mL of acetone was added before measuring absorbance at l = 470, 644.8, and 661.8 nm to calculate the chlorophyll and carotenoid contents as described (Toledo-Ortiz et al, 2010).…”
Section: Methods Plant Materials Growth Conditions and Measurementsmentioning
confidence: 99%
“…The quantitative RT-PCR (qRT-PCR) analysis was performed as described with minor variations (Toledo-Ortiz et al, 2010). Total RNA was isolated from 4-d-old dark-grown seedlings using the Spectrum Plant Total RNA Kit (Sigma-Aldrich).…”
Section: Rna Extraction and Quantitative Rt-pcrmentioning
confidence: 99%
“…First, although they appear to represent a minority, a significant number of PIFq-bound genes are upregulated in pif mutants especially during the deetiolation response ( Figure 2C; Oh et al, 2009Oh et al, , 2012Zhang et al, 2013), suggesting that PIFs act as transcriptional repressors of these genes. Second, evidence for PIFs acting as intrinsic transcriptional repressors of specific genes has been provided in a number of cases, such as PIF1 repression of PSY expression in the dark (Toledo-Ortiz et al, 2010), PIF7 repression of CBF2 expression under diurnal conditions (Kidokoro et al, 2009;Lee and Thomashow, 2012), and PIF1 and/or PIF3 repression of genes associated with chlorophyll biosynthesis, photosynthesis, and reactive oxygen species (ROS) responses during deetiolation (Chen et al, 2013;Liu et al, 2013b). Collectively, the data are consistent with a model whereby in environments with low or absent phy activation, PIFs accumulate and either activate the expression of PIF-induced genes or inhibit the expression of PIF-repressed genes, and this activity is rapidly reversed by light through phy-induced degradation of the PIFs (Figures 3A and 3B).…”
Section: Modes Of Transcriptional Regulation By the Pifsmentioning
confidence: 99%